Systematic and detailed analysis of behavioural tests in the rat Middle Cerebral Artery Occlusion (MCAO) model of stroke: tests for long-term assessment - Trueman, Rebecca C.; Diaz, Claris; Farr, Tracy D.; Harrison, David J.; Fuller, Anna; Tokarczuk, Paweł F.; Stewart, Andrew J.; Paisey, Stephen J.; Dunnett, Stephen B. (Nature Publishing Group, 2016)
In order to test therapeutics, functional assessments are required. In pre-clinical stroke research, there is little consensus regarding the most appropriate behavioural tasks to assess deficits; especially when testing over extended times in milder models with short occlusion times and small lesion volumes. In this study we comprehensively assessed 16 different behavioural tests, with the aim of identifying those that show robust, reliable and stable deficits for up to 2 months. These tasks are regularly used in stroke research, as well as being useful for examining striatal dysfunction in models of Huntington’s and Parkinson’s disease. Two cohorts of male Wistar rats underwent the intraluminal filament model of MCAO (30min) and were imaged 24hrs later. This resulted in primarily subcortical infarcts, with a small amount of cortical damage. Animals were tested, along with sham and naïve groups at 24hrs, 7 days, and 1 and 2 months. Following behavioural testing, brains were processed and striatal neuronal counts were performed alongside measurements of total brain and white matter atrophy. The staircase, adjusting steps, rotarod and apomorphine induced rotations were the most reliable for assessing long-term deficits in the 30 min transient MCAO model of stroke.